1998
DOI: 10.1002/(sici)1521-4109(199805)10:6<403::aid-elan403>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Constant Current Chronopotentiometric Stripping Analysis of Bioactive Peptides at Mercury and Carbon Electrodes

Abstract: Constant current derivative chronopotentiometric stripping analysis (CPSA) was used to study bioactive peptides [Lys 8 ]-vasopressin and angiotensin II at carbon paste electrode (CPE) and hanging mercury drop electrode (HMDE). Both peptides contain a single tyrosine residue which is oxidized at CPE close to þ0.6 V (against Ag/AgCl/3 M KCl electrode) producing peak Y; this peak was by about 15 mV more positive in vasopressin than in angiotensin II. At HMDE vasopressin yielded peak S due to the reduction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(53 citation statements)
references
References 41 publications
1
51
0
1
Order By: Relevance
“…Constant-current chronopotentiometric stripping analysis (CPSA) for the determination of catalytic groups. CPSA produces a well-resolved catalytic peak (so called peak 'H') (Tomschik et al 1998) that is characteristic for peptides and proteins at nanomolar concentrations (Ostatná et al 2007). In CPSA the potential of the catalytic reaction peak (Ep) and its height (dE/dt) -1 depend primarily on the molecular structure, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Constant-current chronopotentiometric stripping analysis (CPSA) for the determination of catalytic groups. CPSA produces a well-resolved catalytic peak (so called peak 'H') (Tomschik et al 1998) that is characteristic for peptides and proteins at nanomolar concentrations (Ostatná et al 2007). In CPSA the potential of the catalytic reaction peak (Ep) and its height (dE/dt) -1 depend primarily on the molecular structure, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…This technique can also be applied for the analysis of DNA and proteins (Palecek et al, 1997a;Tomschik et al, 1998). Measurements were performed with an AUTOLAB (EcoChemie, Utrecht, The Netherlands) connected to a Metrohm 647 VA Stand (mercury electrode) in HMDE mode (drop surface area 0.4 mm 2 ) at a constant current of 71 mA using 0.2 M sodium phosphate as a background electrolyte.…”
Section: Blotting With Immunodetection Of P53mentioning
confidence: 99%
“…The first label-free electrochemistry of proteins came from mercury electrodes. Peptides and proteins containing cysteine/ cystine showed specific electrochemical signals on mercury electrodes with the help of Hg-S bond formation (Havran et al, 2004;Palecek and Ostatna, 2007), reduction of disulfide groups (Tomschik et al, 1998), and the catalytic evolution of hydrogen in cobalt containing solutions (Brdicka reaction) (Brdicka, 1933;Heyrovsky, 2004). Fan et al (2011), who reported Nafion/TiO 2 / graphene/GCE electrode for response to the amino acids L-tryptophane and L-tyrosine with 0.7 and 2.3 mM LODs, and a sensitivity of 75.9 and 22.8 mA mM À 1 , respectively.…”
Section: Mnppf For Amino Acids and Proteins Detectionmentioning
confidence: 99%